2007
DOI: 10.1007/s00520-007-0258-3
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine symptom assessment in women with breast cancer: what a simple “yes” means

Abstract: Patients' experience of endocrine symptoms needs to be considered both in patient care and research, when interpreting the association between symptoms and QL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…However, as it includes elements of an intangible nature, for example, guilt, hopelessness, and fear, its quantification could be difficult. Subjective aspects, such as fear of medication supply running out, the meaning attributed to side‐effects, beliefs about a medication's effectiveness and beliefs about the impact of medication on health and well‐being (e.g. believing that medication is harmful and addictive), were associated with increased levels of treatment burden …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as it includes elements of an intangible nature, for example, guilt, hopelessness, and fear, its quantification could be difficult. Subjective aspects, such as fear of medication supply running out, the meaning attributed to side‐effects, beliefs about a medication's effectiveness and beliefs about the impact of medication on health and well‐being (e.g. believing that medication is harmful and addictive), were associated with increased levels of treatment burden …”
Section: Resultsmentioning
confidence: 99%
“…Bernhard et al 13 Switzerland/ Italy n = 249 patients in a trial for the prophylaxis for delayed emesis Quantitative survey and diary cards Ribi et al 16 Switzerland n = 373 women with early or advanced breast cancer Quantitative survey Yoon et al 47 USA n = 1,219 women with breast cancer Quantitative survey Ow 33 Singapore n = 22 parents from 20 families with children with childhood cancer…”
Section: Quantitative Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…It only focuses on the incidence of an event without grading its severity. In addition to the C-PET, International Breast Cancer Study Group (IBCSG)/Linear Analogue Self-Assessment Scales were utilized to address the side effects of hormonal therapy and treatment burden, the results being discussed elsewhere [6]. …”
Section: Methodsmentioning
confidence: 99%
“…Endocrine symptoms may substantially influence the QoL of the patients when they receive adjuvant endocrine treatment for breast cancer. [10] Høybye[11] reported that breast cancer patients ( n = 1051) suffered from cancer- or cancer treatment-related effects. Many of these patients experienced fatigue (66%), lack of concentration (46%), and joint or muscle pains (49%).…”
Section: Resultsmentioning
confidence: 99%